(3GdJMQjQs - (3CHh WGdH jMji Hf GdMSjf Hf gGQhf GdgGQhfj,J (B404 (3g` s ((3eMeO Hf jMji Hf Sde Hf jMji Hf GdMSf Hf YHO Gddg s)
(3ChdgG (B:s
(3TYQg Ch bde CXGajQg HYO eG JhVF s
(3BNQgG (B:s
(3BNQg ef HGH (B: (3PcQ ef de jMce dQOJg hCMcGe GdeQJOjf bhdg aEf GSde Ndi SHjdg , hEf CHG bJd hdG jSJQb , hEf cGf cGaQkG ai GdCUd hdMb HOGQ GdMQH HYdi caQg ESJQb Je GdcJGH s
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B141s
(3JHUQGJ GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis